Need Analysis untuk Pengembangan Bahan Ajar Mata Kuliah Public Speaking and Presentation - Shanti Sari Dewi, Anak Agung Sagung; Weddha Savitri, Putu (Udayana University, 2025)
Conducting a need analysis before designing teaching materials is perceived as crucial. Hence, this research was conducted and aimed at: 1) identifying the learning needs of students in the course of Public Speaking and Presentation; and 2) analyzing the existing gaps between the student learning needs and the ongoing learning process. This study applied a qualitative approach and involved as many as 77 students in the Public Speaking and Presentation classes in Bachelor of English department, Faculty of Humanities at Udayana University as respondents. The results show that the teaching materials should consist of topics focus on 1) aspects of competent, regular and dynamic public speaking skills; 2) overcoming confidence issues when speaking in public; 3) participating in group discussions, classes and seminars; 4) public speaking for the sake of entertainment and business; and 5) public speaking to influence others and in society.